THE EFFECTIVENESS OF SILENT VIDEO ON STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT IN THE SECOND SEMESTER STUDENTS OF UNIVERSITAS BHINNEKA PGRI - Rivaldo Riyandi Satria Nugraha; Moh. Choirul Huda (Sindoro: Cendikia Pendidikan, 2024)
Students' difficulties in writing narrative texts, especially in understanding and using appropriate grammatical structures and distinguishing narrative texts from other types of text. This research aims to test the hypothesis that Charlie Chaplin's silent videos can be an effective medium for improving students' ability to write narrative texts. It is hoped that this research can contribute to the development of writing learning methods that are more innovative and interesting for students. The design of this research is one-group pre-test post-test to evaluate the effect of silent videos on the ability to write narrative texts of second semester students at Bhinneka PGRI University. A sample of 22 second semester students was selected using purposive sampling to take the pre-test and post-test using the narrative text writing test instrument. The data collected from the test was then analyzed using the paired sample t-test method. The findings from this research study are that the use of silent Charlie Chaplin videos has proven to be effective in improving the narrative text writing skills of second semester students at Bhinneka PGRI University. This is evidenced by a significant increase in students' narrative text writing scores after the silent video intervention, which can be seen from the statistically significant difference in the average pre-test and post-test scores. Silent videos are able to improve students' abilities in terms of using grammatical structures, vocabulary and text organization, as well as motivating them to improve their writing skills. This finding is in line with previous research which shows the effectiveness of silent videos as a writing learning medium.